Synthesis and characterization of flower-like MoO3/In2O3 microstructures for highly sensitive ethanol detection. Issue 38 (28th April 2017) - Hu, Jie; Wang, Xiu; Zhang, Meng; Sun, Yongjiao; Li, Pengwei; Zhang, Wendong; Lian, Kun; Chen, Lin; Chen, Yong
Abstract : A gas sensor was fabricated to measure the response to 100 ppm ethanol at different working temperatures. Abstract : Flower-like pure and Mo-loaded In2 O3 hierarchical microstructures were synthesized by a facile hydrothermal method. The morphology, crystal structures, and compositions of the samples were characterized by SEM, XRD, TEM, showing nanosheets with dimensions of 4 μm diameter and 25 nm thickness. Gas sensing experiments were conducted on the as-prepared MoO3 /In2 O3 gas sensors, and the results prove that Mo-loaded In2 O3 gas sensors exhibit enhanced gas sensing properties at 185 °C. In particular, the 3 mol% Mo-loaded In2 O3 provided a high response (7 to 100 ppm ethanol), fast response and recovery time (11 s and 94 s), low detection limit (50 ppb), good selectivity and stability for ethanol detection, which is promising for low concentration ethanol detection in practical applications.